Participation in Clean Development Mechanism (CDM) Projects/Landfills in the Metropolitan Area of the City of São Paulo - Cruz, Silvia Stuchi; Paulino, Sônia Regina; Paiva, Delhi Teresa (Sustainability in Debate, 2015)
This article proposes an evaluation of stakeholder participation in the context of the Clean Development Mechanism (CDM) landfill projects in São Paulo Metropolitan Area with the purpose of identifying the gaps to achieve genuine service innovation in the urban solid waste sector. International and national literature shows that the involvement of users/citizens - especially of the communities living close to the landfills - in CDM urban solid waste sector projects is still marginal and that CDMs still need to generate co-benefits in the urban solid waste sector. Service innovation is contemplated through the public-private service innovation networks theoretical approach (ServPPIN). This approach explores the organizational and relational aspects (interfaces and feedbacks) among public and private actors, while highlighting the participation of associations and nongovernmental organizations. Six CDM landfill projects located in São Paulo Metropolitan Area were selected as the focus of this research. In order to analyze the participation of the surrounding communities, a set of 16 indicators are proposed. The indicators were grouped in three main topics: consultation; interaction/ interface; and benefits. The construction of the set of indicators was participatory and took into account associations and waste pickers cooperatives surrounding the studied landfills. The resulting indicators contribute to the evaluation of a wide range of factors that are limiting and affecting the promotion of service innovation in the urban solid waste sector supported by the participation of stakeholders.